Implementation of act 171 of 1976 on property assessment for rating systems in Peninsular Malaysia - Muhammad, Habibu Sani (2014)
Property rating is a tax levy on landed properties adjudged rateable by rating authority (Local authorities) in order to raise revenue for providing certain public services and infrastructures as waste collection and disposal, drainage and street cleaning, neighbourhood parks, landscaping and neighbourhood fumigation. Act 171 of 1976 empowers all local authorities in Malaysia to levy property rates based on assessed value of properties (annual or improved value approach) vide sections 127, 129 and 130 respectively. Concurrent application of seemingly unequal approaches triggered a question on possibilities of achieving uniformity as required by the Act. The study was conceptualized to unveil emerging facts from implementation of Act 171 of 1976 on property assessment for rating purpose in peninsular Malaysia with particular reference to achieving uniformity. It was guided by a general research objective: To analyze specific content of the Act affecting property rating and application of international valuation standards in valuation of properties for rating purpose. While the specific objectives include: 1) To compare property classification/rate percentage charges among local authorities 2) To compare rate liabilities between local authorities on annual and improved value approach 3) To identify common reasons advanced in objection hearing sessions by rate payers as well as the processes involved in handling objections by local authorities. The research was conducted on qualitative case study design with interview as the main technique while document analysis, notes and observations were used for triangulation. Eight local authorities of city council status were chosen while respondents/participants were selected from among valuation officers of each local authorities at the inception based on which pilot study was conducted answer the questions thus restructured to only chief valuation officers who well experienced, vast with requisite authority to release documents needed to for triangulation. Findings revealed that, Act 171 of 1976 is wholly applied on issues concerning property rating assessment by the local authorities with divergent practices. They occur are as a result of conflicting provisions in the Act. Misapplication of valuation principles was also identified while failure to comply with provisions of the act in carrying out revaluation of properties is influenced by political reasons as powers to approve or otherwise is vested in the state governments. Property owners were found objecting rate for poor or absence of service provision though hardly considered relaying on past decisions on similar objections however unfair was the decision. The study identified a gap between constituent provisions and policy objective manifesting from the implementation. In order to address this gap, there the need to revisit constituent sections of the act as sections 127, 128, 129, 130, 137, 142, 143, and 144. While a unified implementation system could be achieved through an integrated model of operation designed from research findings.